2017
DOI: 10.2474/trol.12.221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molecular Structure of Zinc Dialkyldithiophosphates on Tribological Properties of a Hydrogenated Amorphous Carbon Film under Boundary Lubrication

Abstract: The effects of the molecular structure of zinc dialkyldithiophosphates (ZDDPs) on the tribological properties of a hydrogenated amorphous carbon (a-C:H) film under boundary lubrication were investigated. Friction tests were performed at a-C:H/a-C:H and steel/steel contacts under lubrication with poly-alpha olefin (PAO) and PAO containing five types of ZDDPs with different alkyl groups (primary-C4 ZDDP, secondary-C4 ZDDP, primary-C6 ZDDP, primary-C8 ZDDP and primary-C12 ZDDP). All our results suggest that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Figure 5 shows the S 2p and P 2p spectra of the sulfur and phosphorus anion-based ionic liquids, respectively. For the sulfur anion-based ionic liquids, the achieve low friction, while those derived from phosphorous achieve low wear volumes [21][22][23][24]. These reaction films were confirmed by XPS analysis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Figure 5 shows the S 2p and P 2p spectra of the sulfur and phosphorus anion-based ionic liquids, respectively. For the sulfur anion-based ionic liquids, the achieve low friction, while those derived from phosphorous achieve low wear volumes [21][22][23][24]. These reaction films were confirmed by XPS analysis.…”
Section: Discussionmentioning
confidence: 61%
“…Sulfur and phosphorus are widely used as extreme-pressure additives, such as zinc dialkyl dithiophosphate (ZDDP) [21][22][23]. These elements exhibit low-friction coefficients, low wear, or both.…”
Section: Sulfur or Phosphorus Anion-based Ionic Liquidsmentioning
confidence: 99%
“…Therefore, it is difficult for the UHV-based analytical techniques to evaluate the chemical characterization of the tribofilms without contamination and their timedependence characterization changes during the friction test. This is why in situ or in-contact analytical approaches are effective for studying tribofilms, as they can easily classify the tribofilm characterization and the time-dependence properties of the tribofilms without washing the samples and removing them from the test rigs [5,[21][22][23][24][25][26][27]. Spikes et al [5,[21][22][23] revealed the tribofilm formation process using a mini traction machinespace layer imaging method (MTM-SLIM), which is a useful tool for monitoring the film thickness of tribofilms on a worn surface.…”
Section: Introductionmentioning
confidence: 99%
“…The SLIM technique can evaluate the thickness of the boundary (tribofilms) and EHD films by using a silica spacer layer-coated glass disk through analyzing interference fringes of the contacts between the glass disk and the steel ball [21][22][23]. On the other hand, we have recently reported that a lab-built in situ Raman tribometer can monitor the time-dependence chemical composition change of the tribofilms on the worn surface without washing the samples and removing them from the test rigs [24][25][26][27]. Chemical characterization and film thickness are important factors for analyzing the tribofilm formation process, as both are strongly related [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on ionic liquids as lubricants focus on fluorine-based ionic liquids, such as tetrafluoroborate, hexafluorophosphate, trifluoromethanesulfonate, and tris(perfluoroalkyl) trifluorophosphate [8][9][10][11][12][13][14][15][16][17]. Zinc dialkyldithiophosphate (ZDDP) is a well-known lubricant additive and exhibites good tribological properties [18][19][20][21][22]. Fluorine-based ionic liquids exhibit superior tribological properties than ZDDP, because of the formation of tribo-films composed of FeF 2 and FeF 3 during sliding [8][9][10][11][12][13][14][15][16][17]23].…”
Section: Introductionmentioning
confidence: 99%